1998
DOI: 10.1002/(sici)1521-3757(19980918)110:18<2651::aid-ange2651>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduzierte Herstellung und Strukturierung von selbstorganisierten Monoschichten mit 1-Alkenen und Aldehyden auf Siliciumhydrid-Oberflächen

Abstract: Die direkte laterale Strukturierung beim Aufbau von selbstorganisierten Monoschichten (SAMs) auf Silicium gelingt durch die photoinduzierte Reaktion von Aldehyden mit Si(111)‐H‐Oberflächen mit der gebräuchlichen Maskentechnik (siehe schematische Darstellung; im rechten Bildteil ist die Mikroskop‐Aufnahme einer strukturierten SAM mit Octadecanal gezeigt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…The mechanism for UV‐induced hydrosilylation involves photolytic homolysis of a surface SiH bond, for example, a radical‐induced reaction. Based on the SiH bond dissociation energy on a silicon surface, a wavelength of shorter than 3501922–380 nm23 is necessary to obtain surface silicon radicals on H‐terminated flat Si(111), which implies that a radical‐based initiation is not in operation during the visible‐light‐promoted hydrosilylation reaction described here. Stewart, Buriak, and co‐workers proposed an alternative mechanism to explain the white‐light‐promoted hydrosilylation of photoluminescent nanocrystalline silicon 14.…”
Section: Static Water Contact Angles Of Monolayers On Silicon Surfacementioning
confidence: 99%
“…The mechanism for UV‐induced hydrosilylation involves photolytic homolysis of a surface SiH bond, for example, a radical‐induced reaction. Based on the SiH bond dissociation energy on a silicon surface, a wavelength of shorter than 3501922–380 nm23 is necessary to obtain surface silicon radicals on H‐terminated flat Si(111), which implies that a radical‐based initiation is not in operation during the visible‐light‐promoted hydrosilylation reaction described here. Stewart, Buriak, and co‐workers proposed an alternative mechanism to explain the white‐light‐promoted hydrosilylation of photoluminescent nanocrystalline silicon 14.…”
Section: Static Water Contact Angles Of Monolayers On Silicon Surfacementioning
confidence: 99%
“…Since 1993 when Linford et al 6) reported the method to form SAMs on Si substrates without an interfacial insulator, that is, SAMs directly attached to Si, several processes to form such SAMs have been developed. 7) While Linford et al employed 1-alkenes as precursors which reacted with a hydrogen-terminated Si (H-Si) substrate in order to form directly-attached SAMs, alcohols 8) and aldehydes 9) have also been shown to form similar SAMs on a H-Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Differenz-Transmissions-FT-IR-Spektren, die vor und nach der Hydrosilylierung aufgenommen wurden, weisen deutlich auf eine Abnahme der Zahl von Si-H-Bindungen hin. Das Weiûlicht bedingt möglicherweise die Spaltung schwacher Si-H-Bindungen an der Oberfläche [13,19] oder die Bildung photogenerierter Löcher, so daû Siliciumradikale entstehen, die anschlieûend von Alken-oder Alkin-Nucleophilen angegriffen werden. [20,21] Bei elektronenarmen Alkinen (Phenylacetylen, 4-Methylphenylacetylen und 4-Chlorphenylacetylen) sind längere Reaktionszeiten nötig (12 h), was für einen Mechanismus mit nucleophilem Angriff spricht.…”
Section: Si Si Si Si Si Siunclassified
“…Transmetallierungen [8] mit Grignard-und Alkyllithium-Verbindungen wurden in Kombination mit Lewis-Säure-Katalysatoren [9] eingesetzt, um die vielen Si-H-Bindungen auf der Oberfläche zu nutzen. Thermische, [10] Radikal-vermittelte [11] und UVphotolytische [12,13] Alken-Hydrosilylierungen an ebenen Si(100)-und Si(111)-Hydridoberflächen sind bereits beschrieben worden.Wir berichten hier über eine effiziente Funktionalisierung der por-Si-Oberfläche durch Hydrosilylierung von ungesättigten C-C-Bindungen unter Weiûlicht bei 25 8C (Schema 1). Schema 1.…”
unclassified
See 1 more Smart Citation